Penggunaan Media Grafis (Peta Konsep) Dalam Pembelajaran Sejarah Untuk Mempermudah Pemahaman Siswa Kelas V Mi Darul Ulum Bojonegoro - Yulia Pramusinta (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Abstract: The teaching medium is a knowledge of the teaching methods used by a teacher or instructor. Methods are the means used to achieve the established goals. Another technique is the presentation technique that is mastered by the teacher to teach or present the lesson materials to the students in the classroom, so that the lesson can be absorbed, understood and used by the students well. The better the teaching method, the more effective the achievement of the goal. Motivation is a change of energy within a person characterized by the emergence of "feeling and preceded by the response to the purpose, to get it then must be selected methods that if acceptable in teaching and learning activities well. In fact, the way or method of teaching used to convey different information in the way adopted to establish students in mastering knowledge, skills and attitudes (cognitive, psychomotoric, affective). Specific methods of teaching in the classroom, the effectiveness of a method is influenced by the purpose, student factors, situation factors, and teacher factor itself. Demonstration is a teaching method done by a teacher or someone else by showing the whole class about a process or a way of doing something. Demonstrations are always directed to the correct way of practice which is then Apliskasikan in everyday life. And recitation is also one of the learning media known as homework or students are given the task outside of lesson time. Both methods can be implemented simultaneously in the teaching and learning process.From the above statements can be concluded that in learning, students so as not to get bored then there should be variations in learning methods. Teachers must be clever in choosing a method, one of which is the Graphic method (concept map). In this case on the history of the use of Graphic method (concept map) is the right method to invite students to think and understand and apply in everyday life. Graphical Pendekata (konse map) invites us to make learning process more meaningful and conductive.        Kewords: Grafis Media, Learning History, Student Chomprehensif